Design of new energy vehicle exhibition space based on virtual reality technology - Huang, Sihua; Mohd Ali, Noor Azizi; Shaari, Nazlina; Mat Noor, Mohd Sallehuddin (Elsevier, 2022)
At present, although the new energy vehicle experience center presents a dynamic development trend of science, technology, diversity and innovation, the display and dissemination of the new energy vehicle industry and culture cannot be satisfied, resulting in the display function cannot be fully exerted. VR (Virtual Reality) display design is a new topic of audio–visual​ design with the popularization of VR technology and related computer application technology. This paper focuses on the realization and application of VR exhibition space design for new energy vehicles, and discusses the design principles that should be followed in VR exhibition space design for new energy vehicles and its practical significance to design communication. In this paper, a parallel 3D reconstruction method based on multi-view video stream is proposed. In this method, the mobile terminal and the server execute asynchronously, the terminal decodes the multi-view video stream in parallel, and the server performs feature extraction and stereo matching on the returned key frames. Finally, the calculated parallax is combined with the projection matrix to restore the 3D scene.